Geomechanical Model Experiment Study on Deformation and Failure Mechanism of the Mountain Tunnel in Layered Jointed Rock Mass. (13th February 2021) - Guo, Zhibiao; Fan, Jinyan; Wang, Fengnian; Zhou, Hongbo; Li, Wei
Abstract : The Minxian tunnel is a key engineering of the Weiyuan-Wudu expressway that is excavated in layered jointed carbonaceous slate rock mass. During the construction process, the surrounding rocks of the tunnel encountered serious large deformations and failure, which brought about great difficulties to the safety and cost of the tunnel. In order to study the deformation and failure mechanism of the surrounding rocks, a physical model test was conducted, and integrated methods including strain gauges, a digital camera, and noncontact full-field digital imaging correlation technique were used to record the response information of the surrounding rocks. The evolution process of surrounding rocks failure was simulated successfully in the model test, and the deformation characteristics were basically consistent with the actual engineering. The modelling results show that concentrated stresses in the surrounding rocks were very uneven due to developed stratified and jointed rock mass structure. The maximum and minimum concentrated stresses appeared at the vault of the tunnel and left of inverted arc area, and concentration factors were 3.11 and 1.98, respectively. The main forms of surrounding rocks deformation and failure were large area spalling of surface, severe circumferential fractures, serious bending deformations of thin rock layers, and collapse of overlying strata. The maximum displacements occurred at left sidewall and right shoulder of the tunnel and the corresponding actual displacements were 460 mm to 500 mm. Caving and failure took place firstly at several key positions with maximum concentrated stresses or displacements and subsequently gave rise to massive collapse of surrounding rocks.